2022
DOI: 10.3389/fchem.2022.849801
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene Derivatives as Ligands for Highly Luminescent and Stable Manganese-Doped CsPbCl3 Nanocrystals

Abstract: Ligands on the surface of perovskite nanocrystals are important to stabilize the nanocrystal structure. However, the research of ligands on Mn2+ ion-doped CsPbCl3 nanocrystals (Mn: CsPbCl3 NCs), a promising candidate family for the lightning community, is relatively rare. Here, we demonstrate a new ligand modification strategy for preparing high-quality Mn: CsPbCl3 NCs by a simple hot-injection method. Thiophene derivative, for the first time, is applied as ligands for perovskite nanocrystals. The new ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To address the above issues and develop a multifunctional ligand that can both achieve surface passivation and improve carrier transport, we investigated thiophene functional groups with electron-donating properties. The high polarization of its sulfur atom causes looser binding of valence π electrons to the aromatic ring, resulting in higher charge mobility. , Additionally, the S atom in the thiophene ring can coordinate with uncoordinated Pb 2+ to passivate defects. , Therefore, by designing ligand molecules and using this characteristic, it is possible to achieve a multifunctional ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the above issues and develop a multifunctional ligand that can both achieve surface passivation and improve carrier transport, we investigated thiophene functional groups with electron-donating properties. The high polarization of its sulfur atom causes looser binding of valence π electrons to the aromatic ring, resulting in higher charge mobility. , Additionally, the S atom in the thiophene ring can coordinate with uncoordinated Pb 2+ to passivate defects. , Therefore, by designing ligand molecules and using this characteristic, it is possible to achieve a multifunctional ligand.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Additionally, the S atom in the thiophene ring can coordinate with uncoordinated Pb 2+ to passivate defects. 32,33 Therefore, by designing ligand molecules and using this characteristic, it is possible to achieve a multifunctional ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many metal ions and additives have been employed to enhance the PLQY and energy transfer of Mn-doped CsPbCl 3 PNCs. Luo et al reported an interesting finding: tuning of dual-color emission of Mn-doped CsPbCl 3 PNCs by post-synthesis treatment with a series of sulfonate ligands; however, the PLQY and stability of the synthesized PNCs after passivation were not studied . Wang et al demonstrated that adding 3-thienylboronic acid during synthesis can improve the PLQY and thermal, self, and purification stabilities of Mn-doped CsPbCl 3 …”
Section: Introductionmentioning
confidence: 99%
“…28 Wang et al demonstrated that adding 3-thienylboronic acid during synthesis can improve the PLQY and thermal, self, and purification stabilities of Mn-doped CsPbCl 3 . 29 Photoluminescence is a surface phenomenon; thereby, surface treatment is a promising technique for producing defect-free PNCs with improved optical characteristics. Several reports are available on the surface treatment of PNCs with various organic additives such as trioctylphosphine (TOP), 30,31 trioctylphosphine oxide (TOPO), 32 benzoic acid, 33 2,2′iminodibenzoic acid, 11 zwitterions, 34 octyl phosphonic acid, 35 dodecane thiol, 36 thiocyanate, 37 thiosulfate, 38 and tetrafluoroborate.…”
Section: Introductionmentioning
confidence: 99%